The spectrum of BRCA1 and BRCA2 mutations in breast cancer patients in the Bahamas. (5th April 2013) - Akbari, MR; Donenberg, T; Lunn, J; Curling, D; Turnquest, T; Krill‐Jackson, E; Zhang, S; Narod, SA; Hurley, J
Abstract We sought to identify the full range of founder mutations in BRCA1 and BRCA2 in the Bahamas and to estimate the proportion of all BRCA1 and BRCA2 mutations that are accounted for by founder mutations. We studied 214 Bahamian women with invasive breast cancer, unselected for age or family history. A founder mutation had previously been identified in 49 patients. We conducted full sequencing of the BRCA1 and BRCA2 genes and multiplex ligation‐dependent probe amplification (MLPA) for 156 patients. A novel founder mutation in BRCA2 (exon 17 818delA) was seen in four different patients and five other unique mutations in BRCA1 and BRCA2, including a large deletion (exons 8–9) in BRCA1. In total, a mutation was seen in 58 of the 214 patients (27%); 92% of carriers carried one of the seven founder mutations. Approximately 27% of unselected cases of breast cancer in the Bahamian population are attributable to a mutation in BRCA1 or BRCA2, a prevalence which far exceeds that of any other country. The majority of women who carry a mutation in the Bahamas, carry one of the seven founder mutations, making it possible to offer genetic testing to all women at risk for breast cancer in the Bahamas.